THE STRUCTURAL ROLE OF TI IN ALUMINOSILICATE LIQUIDS IN THE GLASS TRANSITION RANGE: INSIGHTS FROM HEAT CAPACITY AND SHEAR VISCOSITY MEASUREMENTS - Roskosz M.; Toplis M.J.; Richet P. (My University, 2004)
The shear viscosities and 1 bar heat capacities of glasses and melts along the 67mol% silica isopleth in the system SiO2-Al2O3-Na2O-TiO2 have been determined in the temperature ranges 780-1140 K and 305-1090 K respectively. Anomalous behaviour of both these properties is observed for compositions rich in TiO2 and/or Al2O3, an observation attributed to liquid-liquid phase separation followed by anatase crystallization. For samples which do not show anomalous behaviour, it is found that the partial molar heat capacity of the TiO2 component previously determined in Al-free compositions reproduces our heat capacities to within 1.3%. Viscosity data show that addition of TiO2 tends to increase viscosity and melt fragility at constant temperature. Furthermore, heat capacity and viscosity data may be combined within the framework of the Adam-Gibbs theory to extract values of the configurational entropy of the liquids and qualitative estimates of the variation of the average energy barrier to viscous flow. Configurational entropy at 900K is inferred to decrease upon addition of TiO2, in contrast to previous results from Al-free systems. The compositional limit separating normal from anomalous behaviour, as well as the data for homogenous melts have been used to constrain the structural role of Ti in these samples. Our data are consistent with a majority of Ti in five-fold coordination associated with a titanyl bond, in agreement with previous spectroscopic studies. Furthermore, we find no evidence for a Ti-Al interaction in our samples, and we are led to the conclusion that Al and Ti are incompletely mixed, a hypothesis consistent with the observed reduction of configurational entropy upon addition of TiO2, suggesting an important role of medium range order in controlling the variations in thermodynamic properties.
Keywords: SILICATE MELTS; ALUMINIUM; TITANIUM; HEAT CAPACITY; VISCOSITY; PHASE SEPARATION; FRAGILITY; ADAM AND GIBBS THEORY; CONFIGURATIONAL ENTROPY